Development of a Medical Specialty Recurring Bibliography—Index of Rheumatology - Ruhl, Mary Jane (1967)
The Index of Rheumatology is a newly-developed, recurring bibliography produced by the Medical Literature Analysis and Retrieval System (MEDLARS) of the National Library of Medicine. It is published semimonthly by the American Rheumatism Association. This report describes preliminary testing of MEDLARS output, modification of MEDLARS Medical Subject Headings (MeSH), and the computer formulation for retrieval of the bibliographic citations comprising the Index.